2009
DOI: 10.1038/ismej.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rhizobacterial community composition in soil suppressive or conducive to tobacco black root rot disease

Abstract: Work on soils suppressive to Thielaviopsis basicola-mediated tobacco black root rot has focused on antagonistic pseudomonads to date. The role of non-Pseudomonas rhizosphere populations has been neglected, and whether they differ in black root rot-suppressive versus -conducive soils is unknown. To assess this possibility, tobacco was grown in a suppressive and a conducive soil of similar physicochemical properties, and rhizobacterial community composition was compared using a 16S rRNA taxonomic microarray. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
157
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 59 publications
8
157
0
3
Order By: Relevance
“…This result was consistent with another study conducted in the Emirate of Ajman in the UAE, where 71.8% of the TCAM use was not through physician prescription or supervision [10]. Similar finding was seen in the study conducted in Palestine.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was consistent with another study conducted in the Emirate of Ajman in the UAE, where 71.8% of the TCAM use was not through physician prescription or supervision [10]. Similar finding was seen in the study conducted in Palestine.…”
Section: Discussionsupporting
confidence: 82%
“…Similar result was observed in Palestine where 45.7% reported using TCAM to slow the progression of diabetes [13]. Nonetheless, this study in addition to others showed that majority of TCAM users were satisfied with the results [2,3,10,11,13]. Despite that, special attention has to be given to those experiencing diabetes side effects.…”
Section: Discussionsupporting
confidence: 54%
“…This indicated that our cycling experiments in the greenhouse could duplicate some taxonomic shifts in bacteria that operate at the field level. Kyselková et al (28) found that taxa of Pseudomonas and Bacteroidetes were higher in soil suppressive to tobacco black rot caused by Thielaviopsis basicola when they used a microarray based on 16S RNA, similar to our results. We further demonstrated that Chryseobacterium and Pseudomonas exhibited inhibitory activities against R. solani in vitro or reduced Rhizoctonia disease in inoculated natural soils (Table 5 and 6).…”
Section: Discussionsupporting
confidence: 80%
“…The diversity of soil microbial communities is important for the capacity of a soil to suppress soilborne plant diseases (26,27). In disease-suppressive soils, some of the indigenous microorganisms protect susceptible crops from certain phytopathogens (28). Some isolates of Mitsuaria and Burkholderia inhibited fungal and oomycete growth in vitro and reduced disease severity in infected tomato (Solanum lycopersicum L.) and soybean (Glycine max L.) seedlings (29).…”
mentioning
confidence: 99%
“…Bacillus spp. (liu et al 2001), Rhodocyclales (loy et al 2005), Alphaproteobacteria (Sanguin et al 2006a), or attempt to cover most bacterial phyla (Brodie et al 2006, Kyselková et al 2009). …”
mentioning
confidence: 99%